Variability of Tropical Cyclone Frequency Over the Western North Pacific in 2018–2020 - Ogata, Tomomichi; Baba, Yuya (Frontiers in Climate, 2021)
In this study, we investigate the tropical cyclone (TC) activity over the western North Pacific (WNP) in 2018–2020 and its relationship with planetary scale convection and circulation anomalies that plays a key role in TC genesis. To extract the sea surface temperature (SST)-forced atmospheric variability, atmospheric general circulation model (AGCM) ensemble simulations forced with the observed SST are also executed. In AGCM experiments, we use two different convection schemes to also investigate the uncertainty in convective parameterization and robustness of the simulated atmospheric response. The observed TC activity and genesis potential showed consistent features. In our AGCM simulation, the updated convection scheme improves the simulation skills of the observed genesis potential and planetary scale convection and circulation features. For example, in September-October-November (SON), significant increase in the genesis potential index over the WNP in SON 2018, WNP in SON 2019, and South China Sea (SCS) in SON 2020, which were not captured in the Emanuel scheme, have been well simulated in the updated convection scheme.